NTC Self-Diagnostic System: Improving Sensor Reliability in Automatic Gearboxes - Bella, Naoufal; Salhi, Nohaila; Bouazaoui, Oussama; El Wardi, Jihad; Briki, Fouad; Lagrat, Ismail (International Review on Modeling and Simulations, 2025)
This article examines the growing importance of sensors in automotive systems, focusing on reliability and safety. Sensors, although essential, can fail, sometimes compromising passenger safety. In order to ensure a correct functioning, a self-diagnostic system has been proposed for the NTC thermistor used in automatic gearboxes. This system enables failures to be detected quickly, ensures the accuracy of oil temperature measurements and records anomalies in a database for subsequent analysis. A detailed methodology is described, including electrical continuity tests and Steinhart-Hart calibration strategies used for thermistors, implemented in MATLAB Stateflow. The tests demonstrate the system's effectiveness in identifying and correcting anomalies, while suggesting possible improvements for predicting future anomalies.